Fungsi dan Ragam Bahasa Indonesia - Yusnianti Nurul Mutmaina; Rahma Ashari Hamzah; Fauzianti Fauzianti (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Indonesian language plays a crucial role as both a national and state language, serving as a unifying tool for the nation, a national identity, and a means of communication in various aspects of life. This paper aims to explain the functions of Indonesian as a national and state language, as well as to identify its variations based on usage context, communication media, and fields of application. The research method employed is a literature review, analyzing various sources related to the functions and variations of the Indonesian language. The findings reveal that Indonesian has dual functions: as a symbol of national pride and an official state communication tool. Additionally, the variations of Indonesian are classified into formal, non-formal, and casual based on usage context; spoken and written based on communication media; and academic, legal, literary, journalistic, and advertising based on fields of application. The implication of this research is the importance of public understanding of the functions and variations of Indonesian to ensure its appropriate use in different contexts, thereby enhancing communication effectiveness and preserving Indonesian as a national identity.